INTERACTION OF LEXICAL SEMANTIC GROUPS IN THE TERMINOLOGICAL VOCABULARY OF THE LANGUAGE - Yusufaliyev Elyorjon Mashrabovich (Journal Park Publishing, 2022)
In this article, the issue of paradigmatic, syntagmatic and functional interaction of lexical semantic groups within the terminological dictionary of the language is analyzed from a scientific point of view.
Keywords: Gnosology, semantics, term, denomination, sema, field, lexical-semantic group